2016
DOI: 10.24200/sci.2016.3960
|View full text |Cite
|
Sign up to set email alerts
|

Supply chain coordination via two-way cooperative advertising contract considering competing retailers

Abstract: This article addresses an optimization problem using Game Theory in an advertising environment, where decisions regarding the advertising expenditure of a supply chain members must be determined. We study a cooperative (Co-op) advertising problem in a channel comprised of one manufacturer and two competing/cooperating retailers. The manufacturer leads the channel and Stackelberg game is played between the echelons. Moreover, the retailers in the downstream echelon can adopt either Collusion or Stackelberg beha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 28 publications
0
3
0
Order By: Relevance
“…So, in order to meet these challenges, different tools and models for representing a material flow as well as the flow of information, sources and system behaviors are required to analyze such systems [23]. What is so important about this issue is the network approach to the flow of resources, information and materials that are almost common feature of all these methods.…”
Section: The Proposed Methodologies For Identifying the Conflictsmentioning
confidence: 99%
“…So, in order to meet these challenges, different tools and models for representing a material flow as well as the flow of information, sources and system behaviors are required to analyze such systems [23]. What is so important about this issue is the network approach to the flow of resources, information and materials that are almost common feature of all these methods.…”
Section: The Proposed Methodologies For Identifying the Conflictsmentioning
confidence: 99%
“…Most studies on cooperative advertising considered monopoly at upstream/downstream echelon so that only one supplier/manufacturer located at the upstream echelon and only one retailer/purchaser exists on the downstream echelon [22,27]. However, a number of researchers developed models of duopoly [28][29][30][31][32] and oligopoly (Jørgensen & Zaccour [33]), in which rivals compete with each other to achieve greater benefits. In this paper, the main focus is on the models which consider a duopoly market.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Considering the investment problem of supply chains, Proch et al [36] built a continuous time model and found that the supplier can encourage manufacturers to raise their investment level by subsidizing a portion of their investment costs to improve the underinvestment problem. In contrast to Proch et al [36], Alaei and Setak [37] proposed that subsidy negotiation can further improve advertising performance by establishing and analyzing the dynamic differential game model. In addition, many scholars proposed that subsidy is not confined to one-way subsidy.…”
Section: Introductionmentioning
confidence: 98%